Primary production dynamics on the Agulhas Bank in autumn. (September 2022) - Poulton, Alex J.; Mazwane, Sixolile L.; Godfrey, Brian; Carvalho, Filipa; Mawji, Edward; Wihsgott, Juliane U.; Noyon, Margaux
Abstract: The Agulhas Bank is a productive shelf sea, supporting important fish stocks, nursery grounds, and spawning sites. Few studies have examined the dynamics of primary production and the physio-chemical conditions that support this productivity during autumn. We report from a 14-day, 51-station survey of the central and eastern (21-27°E) Agulhas Bank in March 2019, during which we examined water-column structure, macronutrients, chlorophyll- a (total and size-fractionated), diatom cell counts and Net Primary Production (NPP). East to west trends were observed, with surface mixed layers (SML) and stratification increasing to the west. Euphotic zones were deeper than the SML, with SML irradiance conditions indicative of favorable light conditions for NPP. On average, surface waters contained ∼1.2 μmol N L −1 of nitrate (nitrate + nitrite; NO3 ) and ∼3 μmol Si L −1 of silicic acid, which contrasts with nutrient deficient subtropical source waters. Surface chlorophyll- a ranged from 0.3 to 5.1 mg m −3, with high values inshore and near the shelf break. Nanoplankton (2–20 μm) dominated size-fractionated chlorophyll- a, with microplankton (>20 μm) contributions increasing to the west. Measurements of NPP were collected at seven stations, ranging from 0.3 to 1.1 g C m −2 d −1, with a statistically significant relationship between integrated NPP and surface chlorophyll- a allowing further estimates of NPP (0.1–1.1 g C m −2 d −1 ). We estimated nitrogen-demand to support NPP, with a comparison to surface NO3 indicating ample nutrients to support daily NPP. Around half of the stations possessed a Subsurface Chlorophyll Maximum (SCM), with chlorophyll- a ranging from 1.7 to 10.3 mg m −3 . Characteristics of the SCM (depth, light level, chlorophyll-to-carbon ratios) showed east to west variability, implying that the mechanisms of SCM formation ranged from in-situ growth (east) to photo-acclimation (west). Highlights: Net primary production (NPP) ranged from 0.3 to 1.1 g C m −2 d −1 during March on the Agulhas Bank. Surface mixed layers on the bank had abundant irradiance and nitrate to support NPP rates. Subsurface chlorophyll maxima (SCM) occurred at 47% of sites, containing 1.7–10.3 mg m −3 . SCM deepened east-to-west, linked to in-situ growth (east) and photo-acclimation (west).